Pendampingan Manajemen Keanggotaan Koperasi - Fauziah, Rossa Amalia; Umarni, Yunita; Setiawan, Muhammad Bayu (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2023)
Cooperative membership management assistance is one solution to the problems faced by the Gakom Cooperative, namely the lack of knowledge related to cooperative members as assets, the dual identity of cooperative members as owners and customers, member participation as owners, member participation as customers, and cooperative membership management. The purpose of this activity is to improve understanding and skills related to effective cooperative membership management. The method of implementing this activity is assistance to the management of the West Sumatra Gakom cooperative online using the Zoom meeting application. The partner in this mentoring activity is the Gambir Anam Koto Mandiri Cooperative in West Sumatra. The evaluation was carried out by assigning tasks to the cooperative management, namely recording cooperative members as assets, recording the identity of cooperative members as owners and customers, distinguishing the role of member participation as owners with member participation as customers, and moving membership recording from manual to computerized, with an increase of 65%.